The Effectiveness of Breadfruit Leaf Ethanol Extract to Reduce Level of Blood Glucose Levels in Mice that Induced by Alloxan - Indriyani, Indriyani; Sarasati, Filia; Nurcahyani, Nuning; Sutyarso, Sutyarso; Busman, Hendri (Jurnal Biologi Tropis, 2025)
Severe hyperglycemia symptoms can be brought on by elevated blood glucose levels. Diabetes mellitus will result if this occurs consistently over a period of years. The aim of this study was to determine the effects of breadfruit leaf extract on blood glucose reduction and the effects of alloxan on mice's weight. Data analysis using ANOVA at 5% confidence interval and LSD (Least Significant Difference) test. The research results showed that the K+ group (which was only induced by alloxan) experienced a significant decrease in blood glucose levels when breadfruit leaf extract was administered. Blood glucose level of mice was found to decrease by 61% (87.60 ± 1.07) at an effective dose of 22.4 mg/grbw/day (P3), which was almost the same as the blood glucose level of K (-) on day 0; in addition, the body weight of mice increased after a hyperglycemic episode when the ethanol extract of breadfruit leaves was administered.